Computer method of description of the technologies and properties of Bi2-Te3 -based thermoelectric materials obtained by the Bridgman method - Rybchakov, D.E.; Serbyn, M.V. (Journal of Thermoelectricity, 2021)
This paper presents the results of the study of literary sources describing the technologies and properties of thermoelectric materials obtained by the Bridgman method. The results of one of the stages of creating a software product for the description of the production technologies and properties of a thermoelectric material based on Bi-Te compounds are given.Bibl.8, Fig.2, Table 1.